Gestalt-Prophetic: The Parenting Method for Early Childhood with Gadgets Addiction - Kusumaningtyas, Wahyu; Aziz Q, Ikhwan; Laili, Nur; Hartati, Sri (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung in collaboration with Asosiasi Bimbingan dan Konseling Indonesia (ABKIN), 2019)
This study was conducted to determine the significance Gestalt-Prophetic on improving parent awareness on parenting method for early childhood with gadget addiction case. This quasi-experimental study was carried out by involving two groups of parents (N = 74) which divided into two groups, control (N = 38) and experiment (N = 36) group. This study uses the scale of parenting behavior (Î± = 0.525) referring to the theory proposed by Baumrind (2005). T-test was used to determine the significant differences between both control and experiment group. The control and experiment group have significant differences after receiving treatment and the increase of mean showed that G-Pro is effective to improve parent awareness on parenting method for early childhood with gadget addiction case. The both educational (t = -2.20, p = < 0.05) and vocational (t = 2.50, p = < 0.05) background showed difference mean and standard deviation. The mean between control and experiment group based on educational background showed the highest difference is senior high school and the lowest is elementary school. Then, mean based on the occupational background the highest difference is entrepreneur and the lowest is teacher.